Modular Programming of Hierarchy and Diversity in Multivariate Polymer/Metal-Organic Framework Hybrid Composites - Feng, Liang; Lv, Xiu-Liang; Yan, Tian-Hao; Zhou, Hong-Cai (Journal of the American Chemical Society, 2019)
The idea that complex systems have a hierarchical arrangement has been widely observed on various scales. In this work, we introduce the concept of modular programming, which emphasizes isolating the functionality of a system into independent, interchangeable modules, to tailor the hierarchy and diversity in these complex systems. Guided by modular programming, a system with multiple compatible components, including modules A, B, C, and so forth, can be constructed and subsequently modified into modules A', B', C', and so forth independently. As a proof of concept, a series of multivariate hierarchical metal-organic frameworks (MOFs) with various compositions, ratios, and distributions were prepared as a compatible system. Sequential click reactions and acid treatments can be utilized to selectively modify a certain modular MOF into a polymer, while other modular MOFs either remain in their original state or dissolve upon treatment. As a result, a series of polymer/MOF composites that traditionally have been viewed as incompatible can be prepared with tailored properties and behaviors. The resulting polymer/MOF hierarchical composites represent a unique porous composite material which contains functional groups and metal clusters with controllable compositions and distribution, tunable hierarchically porous structures, and tailored diversity within one framework. This general synthesis approach guided by modular programming not only provides a facile method to tailor hierarchy and diversity in multivariate systems but also enables the investigation into hierarchy and its structured control flow, which is a critical design feature of future materials for their fast adaptivity and responses to variable environmental conditions.